Resilience, tourism and disasters - Becken, Susanne; Khazai, Bijan (Tourism and resilience, 2017)
This chapter begins by clarifying the link between disasters, vulnerability and resilience. It then continues by discussing a stakeholder-driven initiative that was put in place to proactively advance the resilience of an important sub-sector of tourism, namely tourist accommodation. The case study of the Hotel Resilient Initiative highlights how different types of resilience can be integrated to...